Variasi Kata Sapaan di Lingkungan Sekolah Tahfizh Plus Khoiru Ummah Jember: Kajian Sosiodialektologi - Santuso Santuso; Agus Sariono; Asrumi Asrumi (Yayasan Literasi Sains Indonesia, 2023)
In Indonesian society, individuals use specific forms of address when communicating with each other. The choice of address is influenced by various social factors. This research aims to describe the variations of address used within the community of STP Khoiru Ummah Jember, as well as identify the social factors that influence them. This study employs a qualitative descriptive research design. The data sources for this research are the teachers, staff, and students of STP Khoiru Ummah Jember. The data collected consists of words, phrases, clauses, and sentences containing address terms. Data collection is conducted through face-to-face interviews, while the data analysis employs an extralingual equivalence method. The results of this research indicate that the address terms used by the members of STP Khoiru Ummah Jember consist of the following categories: (a) personal names, (b) second-person pronouns, (c) kinship terms, (d) educational titles, (e) other forms of address, and (f) figurative meanings. The variation in address terms is influenced by several social factors, namely: (a) the conversational situation, (b) ethnic or tribal background, (c) age, (d) familiarity or intimacy, (e) social status, (f) gender, and (g) the origin or background of the interlocutor.